2021
DOI: 10.21037/qims-20-764
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of suspicious ankle instability using the calcaneofibular ligament cross-sectional area

Abstract: Background: An injured calcaneofibular ligament (CFL) is a major cause of ankle instability (AI). Previous research has demonstrated that the thickness of the calcaneofibular ligament (CFLT) is correlated with higher-grade sprains and ankle instability. However, inflammatory hypertrophy is distinct from ligament thickness; accordingly, we considered that the calcaneofibular ligament cross-sectional area (CFLCSA) as a potential morphological parameter to analyze inflammatory CFL. We hypothesized that the CFLCSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In a study by Liu et al, greater ATFL length and thickness were reported in patients with chronic ankle instability [21]. Another study also reported a difference in the thickness of the CFL between patients diagnosed with chronic ankle instability and healthy patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Liu et al, greater ATFL length and thickness were reported in patients with chronic ankle instability [21]. Another study also reported a difference in the thickness of the CFL between patients diagnosed with chronic ankle instability and healthy patients [22].…”
Section: Introductionmentioning
confidence: 99%